REVITALISASI METODE DAKWAH ANAKRONISTIS DAI GENERASI MILENIAL - BOBBY RACHMAN SANTOSO (Universitas Islam Negeri (UIN) Mataram, 2019)
Da'wah in the modern era is very dependent on dai millenial. Dai millennial should preach using methods that are applied to the needs of the community and keep abreast of the times. The method of da'wah that is applied in every activity is supported by modern media that are able to attract the attention of mad'u on a large scale. Advances in technology and modern media make the method of da'wah applied by millennials must be revitalized in order to reach the perfection of da'wah. Especially in this era, people are faced with complex life problems. Dai millennial can combine anachronistic and modernist methods of da'wah in da'wah. Both methods of da'wah can attract people's interest and stop the negative side of the modern era. Millennials are required to understand the situation and condition of honey both sociologically and psychologically in order to find the right method of da'wah.